Selected Phenomena of Spontaneous Electric Noise - Hayk Asatryan; Eugen Grycko; Werner Kirsch (Journal of Advances in Applied & Computational Mathematics, 2016)
Recently a modified Drude model of the valence electron gas in metals was investigated mathematically. The implications of this model suggest that the thermal noise voltage increases for example with the length of the metallic conductor. This observation prompted us to carry out some innovative experiments whose outcomes confirmed qualitatively the Drude model. We discuss some implications of this model in the light of the performed measurements.